Research on soe biocharacteristics of professional dog semen for freservation and artificial insemination - Thu, Do Van; Anh, Nguyen (Academia Journal of Biology, 2014)
The aims of this study was to determine some biocharacteristics of dog semen and to assess the effects of time, environment and others on quality of semen samples. Semen was obtained from professional dog breeds of Berger, Labrador and Cocker at Professional dog research center - Ministry of Public Security. The semen quality of each ejaculate was assessed after collection and the following parameters were determined: volume, pH, sperm concentration, progressive motility, percentage of live spermatozoa and percentage of abnormal spermatozoa. The study was also performed to assess the effects of environmental factors (especially temperature), the period of times between two time of semen collection and the method of semen collection on quality of semen. The results showed that, cold and especially hot weather had negative influence on semen quality. Semen which was collected in summer (from june to august) showed a lower quality (progressive motility, sperm concentration, proportion of live spermatizoa and proportion of abnomal spermatozoa were: 69.00 ± 2.24, 195.47 ± 15.05, 82.26 ± 8.40 and 24.15 ± 3.58, respectively. August 2005) then those in autumn (progressive motility, sperm concentration, proportion of live spermatizoa and proportion of abnomal spermatozoa were: 76.44 ± 9.47, 265.57 ± 53.50, 87.52 ± 8.46 and 16.73 ± 3.9, respectively. November 2005) with cool weather. The period between two times of semen collection and the phase of collection also had a significant effect on semen quality. This study indicated that to obtain semen with high quality, the period between two times of collection might be three days in minimum. We also found that semen which was collected at second phase of ejaculating (progressive motility, sperm concentration, proportion of live spermatizoa and proportion of abnomal spermatozoa were: 74.286 ± 3.450, 318.406 ± 38.617, 84.024 ± 3.770 and 16.686 ± 0.910, respectively) showed a higher quality than was done from all three phases (progressive motility, sperm concentration, proportion of live spermatizoa and proportion of abnomal spermatozoa were: 45.000 ± 7.071, 47.101 ± 18.627, 66.024 ± 4.503 and 16.843 ± 1.751, respectively). These results play an important role on the successful of preservation of dog semen and artificial insemination.